A method for preparing a multilayer gradient-reinforced proton exchange membrane and a product thereof

By employing a multilayer gradient-enhanced proton exchange membrane fabrication method, the problem of performance degradation of proton exchange membranes under humidity/pressure cycling was solved, achieving synergistic optimization of proton conductivity and mechanical strength, and improving the long-term operational stability and interfacial compatibility of the membrane.

CN122417964BActive Publication Date: 2026-08-25SHENZHEN GENERAL HYDROGEN ENERGY TECH CORP LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610875399.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-17
Publication Date
2026-08-25
Estimated Expiration
2046-06-17

AI Technical Summary

Technical Problem

Existing proton exchange membranes exhibit performance degradation under humidity/pressure cycling, making it difficult to synergistically optimize mechanical strength and proton conductivity. They also suffer from weak interfacial bonding and poor long-term operational stability.

Method used

A multilayer gradient-enhanced proton exchange membrane was prepared by coating PFSA resin with different ion equivalents on both sides of the e-PTFE membrane and coating TiO2 on the surface of the PEEK membrane, combined with low-temperature step-drying and high-temperature annealing treatment, to form a multilayer heterogeneous material structure.

Benefits of technology

It significantly improves proton conduction efficiency and mechanical strength, enhances the membrane's resistance to humidity and pressure cycling, improves interlayer bonding, extends service life, and maintains excellent chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122417964B_ABST
    Figure CN122417964B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of proton exchange membranes, and particularly relates to a preparation method of a multilayer gradient enhanced proton exchange membrane and a product thereof. The method comprises the following steps: cleaning and pretreating a base film; preparing a nitrogen / tungsten-based platinum black catalyst and preparing PFSA resin slurry containing the catalyst; coating the PFSA resin slurry on both sides of the e-PTFE film through a slit to obtain a proton conduction layer; irradiating a PEEK film with ultraviolet light and coating the PEEK film with TiO2 sol to form a mechanical enhancement layer; assembling the functional layers into a "sandwich" structure through PFSA resin adhesion; and performing low-temperature gradient drying and high-temperature annealing, and then performing off-line activation to obtain the multilayer gradient enhanced proton exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of proton exchange membrane technology, specifically relating to a method for preparing a multilayer gradient-enhanced proton exchange membrane and its product. Background Technology

[0002] Currently, hydrogen energy, as a green, efficient, and pollution-free secondary energy source, especially proton exchange membranes (PEMs), is attracting much attention. In existing technologies, PEMs continuously face the dual challenges of humidity and pressure. Currently, PTFE is commonly used and modified to improve its mechanical and chemical properties, mainly including surfactant modification and sulfonated PTFE support layer modification.

[0003] However, these single modification methods still have limitations, making it difficult to achieve synergistic optimization of multiple performance indicators such as mechanical strength, proton conductivity, and chemical stability. Furthermore, the weak interfacial bonding and easy peeling between different functional layers in multilayer composite membranes, as well as the performance degradation caused by humidity / pressure cycling during long-term operation, remain unresolved. Therefore, developing a proton exchange membrane that combines high proton conductivity, high mechanical strength, excellent chemical stability, and good interfacial compatibility is of significant practical importance. Summary of the Invention

[0004] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments.

[0005] As one aspect of the present invention, the present invention provides a method for preparing a multilayer gradient-enhanced proton exchange membrane, which includes the following steps: S1: Cleaning and pretreatment of PI base film, e-PTFE membrane and PEEK membrane; S2: Prepare a nitrogen / tungsten-based platinum black catalyst and mix it with PFSA resin to prepare a PFSA resin slurry containing the nitrogen / tungsten-based platinum black catalyst. Then, coat the pure PFSA resin slurry and the PFSA resin slurry containing the nitrogen / tungsten-based platinum black catalyst onto both sides of the e-PTFE membrane, and dry them to obtain a proton-conducting layer. The PFSA resin includes two resins with different ion equivalent ranges: the first resin has an ion equivalent of 720-870, and the second resin has an ion equivalent of 1000-1200. The pure PFSA resin slurry uses the first resin, and the PFSA resin slurry containing the nitrogen / tungsten-based platinum black catalyst uses the second resin. S3: The PEEK film is subjected to ultraviolet light irradiation and TiO2 sol coating, and then dried to form a mechanical reinforcement layer; wherein, the ultraviolet light irradiation time is 5-20 min, and the TiO2 sol is prepared by tetrabutyl titanate, ethanol and water in a volume ratio of 1:5-15:0.5-2. S4: The proton conduction layer of step S2, the mechanical reinforcement layer of step S3, and the PI base film are bonded and assembled with PFSA resin slurry to form a "sandwich" structure composite film. After low-temperature step-by-step drying and high-temperature annealing, the PI base film is removed. S5: Immerse in hydrogen peroxide for activation to obtain a multilayer gradient-enhanced proton exchange membrane.

[0006] As a preferred embodiment of the preparation method described in this invention, the cleaning pretreatment in step S1 includes: first purging with compressed air, then wiping with anhydrous ethanol or acetone, then immersing the e-PTFE membrane and PEEK membrane in hydrogen peroxide for ultrasonic cleaning, and finally washing with deionized water until neutral and drying.

[0007] As a preferred embodiment of the preparation method described in this invention, the preparation process of the nitrogen / tungsten-based platinum black catalyst in step S2 includes: mixing silicon nitride and platinum black catalyst and then subjecting them to high-temperature oxidation calcination, followed by soaking and washing with hydrofluoric acid; then reacting them with sodium metatungstate and urea under acidic conditions in a hydrothermal manner; and finally heating them in a hydrogen / air mixed atmosphere.

[0008] As a preferred embodiment of the preparation method described in this invention, the coating thickness in step S2 is 50-150 μm, and the drying temperature is 50-80℃.

[0009] As a preferred embodiment of the preparation method described in this invention, step S3 includes adding nitric acid to adjust the pH to 3.0 to form TiO2 sol; the drying includes pre-drying at 100-130℃ and then drying at 150-180℃.

[0010] As a preferred embodiment of the preparation method described in this invention, in step S3, after the PEEK film is irradiated with ultraviolet light, the ultraviolet-irradiated PEEK film is immersed in TiO2 sol, and the PEEK film is pulled out from the TiO2 sol at a pulling speed of 5-20 mm / s, dried, and a mechanical reinforcement layer is formed.

[0011] As a preferred embodiment of the preparation method described in this invention, the low-temperature stepped drying in step S4 includes: first drying at 50-70℃ for 20-40 min, then slowly heating to 80-100℃ for 40-80 min, repeating the low-temperature stepped drying process 1-3 times; the high-temperature annealing treatment includes: drying at 130-150℃ for 10-30 min, then annealing at 200-220℃ for 5-20 min; the PFSA resin slurry between the mechanical reinforcement layer and the PI substrate is: dispersing resin with an ion equivalent of 720-870 in a 70wt% ethanol aqueous solution to form a slurry with a solid content of 12.5wt%; the PFSA resin slurry between the mechanical reinforcement layer and the proton conduction layer is: dispersing resin with an ion equivalent of 1000-1200 in a 65wt% ethanol aqueous solution to form a slurry with a solid content of 15wt%; In the "sandwich" structure composite membrane, the side of the proton conduction layer coated with a nitrogen / tungsten-based platinum black catalyst, consisting of PFSA resin slurry, is bonded to the mechanical reinforcement layer.

[0012] As a preferred embodiment of the preparation method described in this invention, the activation in step S5 is as follows: immersing the membrane obtained in step S4 in 5-15wt% hydrogen peroxide at room temperature for 20-60 minutes.

[0013] As a preferred embodiment of the preparation method described in this invention, in step S2, the pure PFSA resin slurry is prepared by dispersing resin with an ion equivalent of 720-870 in a 70wt% ethanol aqueous solution, and its resin solid content is 12.5wt%; the PFSA resin slurry containing nitrogen / tungsten-based platinum black catalyst is prepared by dispersing resin with an ion equivalent of 1000-1200 in a 60wt% ethanol aqueous solution, adding a nitrogen / tungsten-based platinum black catalyst, and its resin solid content is 10.5wt%, and its platinum element content is 0.25wt%.

[0014] The present invention also provides a multilayer gradient-enhanced proton exchange membrane prepared by the above-described preparation method, characterized in that the multilayer gradient-enhanced proton exchange membrane comprises a mechanical reinforcement layer and a proton conduction layer; The mechanical reinforcement layer is a PEEK film with a TiO2 layer on its surface; the proton conduction layer includes an e-PTFE film and PFSA resin layers coated on both sides of the e-PTFE film, wherein one side of the PFSA resin layer is a pure PFSA resin layer and the other side of the PFSA resin layer contains a nitrogen / tungsten-based platinum black catalyst; the side of the proton conduction layer containing the nitrogen / tungsten-based platinum black catalyst is bonded to the mechanical reinforcement layer.

[0015] The beneficial effects of this invention are: (1) The present invention constructs a proton conduction layer by modifying e-PTFE, which significantly improves the proton conduction efficiency. At the same time, TiO2 is coated on the PEEK surface to form a mechanical reinforcement layer, which greatly improves the tensile strength and deformation resistance of the membrane, and realizes the synergistic optimization of proton conduction and mechanical properties.

[0016] (2) By using multi-layer heterogeneous materials for precise assembly and low-temperature step-by-step drying process, a dense and elastic porous structure is formed, which enhances the membrane's tolerance to humidity and pressure cycles and extends its service life.

[0017] (3) Through interface bridging design, the bonding force between functional layers is effectively improved, interlayer delamination is avoided, and the stability and chemical durability of the overall structure are enhanced.

[0018] (4) The proton exchange membrane of the present invention exhibits low gas permeability, high resistance to oxidation and corrosion and excellent long-term operational stability in application. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below, wherein: Figure 1 This is a schematic diagram of a multilayer gradient-enhanced proton exchange membrane. In the diagram, 1 is the PI substrate, 2 is the PEEK1 membrane, and 3 is the e-PTFE1 membrane.

[0020] Figure 2 For electrochemical performance testing.

[0021] Figure 3 This is a durability test for Example 1. Detailed Implementation

[0022] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.

[0023] Example 1: Step 1: Pretreatment: Wipe the PI substrate (Guangboshi), e-PTFE membrane (thickness approximately 12±3μm, DONALDSON, 380124E1), and PEEK membrane (SEFAR, SEFAR PEEKTEX IEM-17-100 / 60150 cm, 50μm) in one direction with a lint-free cloth soaked in anhydrous ethanol. Let stand for 5-15 minutes to allow the ethanol to evaporate.

[0024] Then, the e-PTFE membrane and PEEK membrane were immersed in 10% hydrogen peroxide, ultrasonically soaked in a 60℃ constant temperature water bath for 30 minutes (ultrasonic frequency of 30KHz), washed with deionized water, and dried for later use.

[0025] Step 2: 1. Preparation of catalysts: 1) Silicon nitride (Si3N4, Maclean) was soaked in 1 mol / L NaOH aqueous solution for 10 min, and then mixed with platinum black catalyst (platinum content of about 97%, purchased from Anhui Masuzu Company) at a mass ratio of 1.5:1. The mixture was then placed at the vent of a high-temperature tube furnace, oxygen was introduced, and the temperature was increased to 850°C at a rate of 5°C / min for high-temperature oxidation calcination and held for 2 hours. After that, it was soaked in 3 mol / L HF aqueous solution for 15 min and washed with deionized water 3-5 times to obtain catalyst 1.

[0026] 2) Mix 1 part sodium metatungstate, 1.25 parts urea, and 2 parts deionized water by mass, adjust the pH to 2 with 1 mol / L hydrochloric acid aqueous solution, add 1 part catalyst 1, stir evenly, put into a high-pressure reactor, heat to 350℃ at a heating rate of 5℃ / min, and keep at the temperature for 5 hours to obtain catalyst 2.

[0027] 3) Place catalyst 2 into the vent of a tube furnace and introduce an H2 / Air (volume ratio 3:7) atmosphere. Heat at 300°C for 2 hours to obtain catalyst 3.

[0028] 2. Preparation of PFSA resin slurry and e-PTFE1 membrane: A resin (solvay, D79) with an ion equivalent (EW) of approximately 720-870 was added to a 70 wt% ethanol aqueous solution. The solid content of the resin solution was 12.5 wt%, and this solution was designated as PFSA resin 1. Take a resin (Cholmous, D2020) with an ion equivalent (EW) of about 1000-1200 and add it to a 65wt% ethanol aqueous solution. The solid content of the resin solution is 15wt%, and it is denoted as PFSA resin 2.

[0029] A resin (Cholmous, D2020) with an ion equivalent (EW) of approximately 1000-1200 was added to a 60wt% ethanol aqueous solution, resulting in a resin solution with a solid content of 10.5wt%. Catalyst 3 was added to make the platinum content in the solution 0.25wt%, and this solution was designated as PFSA resin 3.

[0030] 3. Preparation of e-PTFE1 membrane (proton conduction layer): PFSA resin 1 is coated on one side of the e-PTFE membrane with a wet film thickness of 100 μm and dried at 60℃ for 10 min. PFSA resin 3 is coated on the other side of the e-PTFE membrane with a wet film thickness of 100 μm and dried at 60℃ for 10 min. Figure 1 In the middle, 3 is the e-PTFE1 membrane.

[0031] Step 3: The PEEK membrane was irradiated with a Rodani UV100 UV-ozone lamp (wavelength range: 185nm and 254nm, power: 40W) for 10 min. Tetrabutyl titanate, ethanol, and deionized water were mixed at a volume ratio of 1:10:1 and stirred at 300 rpm for 30 min. Nitric acid (volume concentration: 0.5%) was slowly added dropwise to form a titanium dioxide sol. This sol was then immersed in the UV-ozone-irradiated PEEK membrane and pulled out at a speed of 10 mm / s. The membrane was then pre-baked at 120℃ for 10 min and then dried at 160℃ for 10 min to obtain the treated PEEK membrane. PFSA resin 1 was applied to one side of the treated PEEK membrane with a 200µm slit thickness, and then PFSA resin 2 was applied to the other side of the treated PEEK membrane with a 250µm slit thickness to obtain PEEK1 membrane (mechanical reinforcement layer). Figure 1 In the middle, 2 is a PEEK1 membrane.

[0032] Step 4: Select a PI base film of appropriate size, and attach the PEEK1 film onto the PI base film (with the side of the PEEK1 film coated with PFSA resin 1 attached to the PI base film). Then attach the e-PTFE1 film onto the PEEK1 film (with the side of the e-PTFE1 film coated with PFSA resin 3 attached to the PEEK1 film), to obtain a sandwich-structured composite film. Place the composite film in a 60℃ oven for 30 min, then slowly raise the temperature to 90℃ and dry for 60 min. Repeat this process twice. Then raise the oven temperature to 140℃ and dry for 20 min. Finally, perform high-temperature annealing at 210℃ for 12 min to obtain a multilayer gradient-enhanced proton exchange membrane with high mechanical and proton conductivity and strong durability containing a "sandwich" structure (the thickness is approximately 85±5µm after removing the PI base film).

[0033] Step 5: Soak in 10% hydrogen peroxide at room temperature for 30 minutes.

[0034] Comparative Example 1: The difference from Example 1 is that catalyst 3 is not added to the e-PTFE1 membrane, while the rest of the preparation methods are the same as in Example 1.

[0035] Comparative Example 2: Compared with Example 1, step 3 is omitted, and the remaining preparation methods are the same as in Example 1.

[0036] Comparative Example 3: Steps 1-3 are described in Example 1; Step 4: Select a PI base film of appropriate size, and attach the PEEK1 film to the PI base film (wherein, the side of the PEEK1 film coated with PFSA resin 1 is attached to the PI base film), and then attach the e-PTFE1 film to the PEEK1 film (wherein, the side of the e-PTFE1 film coated with PFSA resin 3 is attached to the PEEK1 film), to obtain a sandwich structure composite film. Place the composite film in 140℃ to dry for 20 min, and then perform high-temperature annealing at 210℃ for 12 min. Step 5: See Example 1.

[0037] Comparative Example 4: Compared to Example 1, step 5 is omitted, while steps 1-4 are the same as in Example 1.

[0038] Electrochemical performance testing: The membrane electrode assembly was used for IV performance and electrochemical lifetime testing: A catalyst-coated membrane (CCM) was assembled between a 0.4 mm thick titanium felt anode, a 0.24 mm thick gas diffusion layer (GDL) cathode, and two PTFE gaskets to form a membrane electrode assembly (MEA). The effective electrode area was 25 cm². 2 The platinum loading of the CL anode is 1.0 mgPt / cm³. 2 The platinum loading of the cathode CL is 0.4 mgPt / cm². 2 A 140µm thick gasket was selected for the anode, and a 100µm thick gasket for the cathode. The hardware was tightened to a torque of 8 Nm. The system was tested at 65℃ and a circulating water flow rate of 100 mL / min with a torque of 0 A / cm. 2 -0.5 A / cm 2 -1 A / cm 2 -2 A / cm 2 After activation for 15 minutes, at 2 A / cm 2 Chemical lifetime tests were conducted at a current density exceeding 1000 hours to determine voltage change trends and calculate the performance degradation rate of the CCM.

[0039] IV performance testing was conducted at 65℃ with a circulating water flow rate of 100 mL / min, and a test step size of 0.5 A / cm. 2 Perform the test and record 0 A / cm 2 -1 A / cm 2 -2 A / cm 2 -3 A / cm 2 Corresponding voltage data. All tests were conducted on a PEM water electrolysis test bench. See Figure 2 .

[0040] Durability testing: The test current was set to 2 A / cm under the conditions of 65℃ and 100 mL / min circulating water flow. 2 The corresponding data from the durability tests are as follows. All tests were conducted on a PEM water electrolysis test bench. See [link / reference]. Figure 3 .

[0041] The oxidation and corrosion resistance test procedure is as follows: The prepared proton exchange membrane was cut into corresponding 5 pieces. 5cm 2 Place the membrane in a vacuum drying oven and dry at 80℃ for 30 min to 4 h to ensure surface dryness. Weigh the membrane and record the initial mass m1. Immerse the proton exchange membrane in 3-10% H2O2 reagent for 10-30 min, remove it, rinse it with deionized water, repeat the drying steps, weigh the membrane, and record the mass m2. The oxidation and corrosion resistance is calculated as the percentage of mass loss.

[0042] Oxidation and corrosion resistance (%) = (m 1- m2) / m1.

[0043] Table 1

[0044] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a multilayer gradient-enhanced proton exchange membrane, characterized in that, Includes the following steps: S1: Cleaning and pretreatment of PI base film, e-PTFE membrane and PEEK membrane; S2: Prepare a nitrogen / tungsten-based platinum black catalyst and mix it with PFSA resin to prepare a PFSA resin slurry containing the nitrogen / tungsten-based platinum black catalyst. Then, coat the pure PFSA resin slurry and the PFSA resin slurry containing the nitrogen / tungsten-based platinum black catalyst onto both sides of the e-PTFE membrane, and dry them to obtain a proton-conducting layer. The PFSA resin includes two resins with different ion equivalent ranges: the first resin has an ion equivalent of 720-870, and the second resin has an ion equivalent of 1000-1200. The pure PFSA resin slurry uses the first resin, and the PFSA resin slurry containing the nitrogen / tungsten-based platinum black catalyst uses the second resin. S3: The PEEK film is subjected to ultraviolet light irradiation and TiO2 sol coating, and then dried to form a mechanical reinforcement layer; wherein, the ultraviolet light irradiation time is 5-20 min, and the TiO2 sol is prepared by tetrabutyl titanate, ethanol and water in a volume ratio of 1:5-15:0.5-2. S4: The proton conduction layer of step S2, the mechanical reinforcement layer of step S3, and the PI base film are sequentially bonded and assembled with PFSA resin slurry to form a "sandwich" structure composite film. After low-temperature step-by-step drying and high-temperature annealing, the PI base film is removed. S5: Immerse in hydrogen peroxide for activation to obtain a multilayer gradient-enhanced proton exchange membrane; The multilayer gradient-enhanced proton exchange membrane includes a mechanical reinforcement layer and a proton conduction layer. The mechanical reinforcement layer is a PEEK membrane with a TiO2 layer on its surface. The proton conduction layer includes an e-PTFE membrane and PFSA resin layers coated on both sides of the e-PTFE membrane. One side of the PFSA resin layer is a pure PFSA resin layer, and the other side of the PFSA resin layer is a PFSA resin layer containing a nitrogen / tungsten-based platinum black catalyst. The side of the PFSA resin layer containing the nitrogen / tungsten-based platinum black catalyst in the proton conduction layer is bonded to the mechanical reinforcement layer.

2. The preparation method according to claim 1, characterized in that, The cleaning pretreatment described in step S1 includes: first purging with compressed air, then wiping with anhydrous ethanol or acetone, then immersing the e-PTFE membrane and PEEK membrane in hydrogen peroxide for ultrasonic cleaning, and finally washing with deionized water until neutral and drying.

3. The preparation method according to claim 1 or 2, characterized in that, The preparation process of the nitrogen / tungsten-based platinum black catalyst in step S2 includes: mixing silicon nitride and platinum black catalyst and then subjecting them to high-temperature oxidation calcination, followed by soaking and washing with hydrofluoric acid; then reacting them with sodium metatungstate and urea under acidic conditions in a hydrothermal environment; and finally heating them in a hydrogen / air mixed atmosphere.

4. The preparation method according to claim 1 or 2, characterized in that, In step S2, the coating thickness is 50-150 μm, and the drying temperature is 50-80℃.

5. The preparation method according to claim 1 or 2, characterized in that, Step S3 includes adding nitric acid to adjust the pH to 3.0 to form TiO2 sol; the drying includes pre-drying at 100-130℃ and then drying at 150-180℃.

6. The preparation method according to claim 5, characterized in that, In step S3, after the PEEK film is irradiated with ultraviolet light, the ultraviolet-treated PEEK film is immersed in TiO2 sol and pulled out from TiO2 sol at a pulling speed of 5-20 mm / s, then dried to form a mechanical reinforcement layer.

7. The preparation method according to claim 1 or 2, characterized in that, The low-temperature stepped drying in step S4 includes: first drying at 50-70℃ for 20-40 minutes, then slowly raising the temperature to 80-100℃ and drying for 40-80 minutes, repeating the low-temperature stepped drying process 1-3 times; the high-temperature annealing treatment includes: drying at 130-150℃ for 10-30 minutes, then annealing at 200-220℃ for 5-20 minutes; The PFSA resin slurry between the mechanical reinforcement layer and the PI substrate is prepared by dispersing a resin with an ion equivalent of 720-870 in a 70wt% ethanol aqueous solution to form a slurry with a solid content of 12.5wt%; the PFSA resin slurry between the mechanical reinforcement layer and the proton conduction layer is prepared by dispersing a resin with an ion equivalent of 1000-1200 in a 65wt% ethanol aqueous solution to form a slurry with a solid content of 15wt%. In the "sandwich" structured composite membrane, the side of the proton conduction layer coated with a nitrogen / tungsten-based platinum black catalyst, consisting of PFSA resin slurry, is bonded to the mechanical reinforcement layer.

8. The preparation method according to claim 1 or 2, characterized in that, The activation in step S5 is as follows: immerse the membrane obtained in step S4 in 5-15 wt% hydrogen peroxide at room temperature for 20-60 minutes.

9. The preparation method according to claim 1 or 2, characterized in that, In step S2, the pure PFSA resin slurry is made by dispersing resin with an ion equivalent of 720-870 in a 70wt% ethanol aqueous solution, and its resin solid content is 12.5wt%; the PFSA resin slurry containing nitrogen / tungsten-based platinum black catalyst is made by dispersing resin with an ion equivalent of 1000-1200 in a 60wt% ethanol aqueous solution, adding nitrogen / tungsten-based platinum black catalyst, and its resin solid content is 10.5wt% and platinum element content is 0.25wt%.

Citation Information

Patent Citations

  • Preparation method of enhanced proton exchange membrane based on surface modified polymer skeleton

    CN113314748A

  • Membrane electrode structure for fuel cell, method for preparing membrane electrode for fuel cell, and proton exchange membrane fuel cell system

    WO2020252606A1